59.3k views
2 votes
Anyone know the answer? Much appreciate the help!!

Anyone know the answer? Much appreciate the help!!-example-1
User Muneikh
by
5.4k points

1 Answer

3 votes

Answer:


x=3+\frac{\sqrt{4L^(2)+1}}{L} and
x=3-\frac{\sqrt{4L^(2)+1}}{L}

Explanation:

we have


L=\frac{1} {√(x^2-6x + 5)}

Solve for x

That means-----> isolate the variable x

squared both sides


L^(2) =(\frac{1} {√(x^2-6x + 5)})^(2)\\ \\L^(2)=\frac{1} {{x^2-6x + 5}}\\ \\x^2-6x + 5=(1)/(L^(2))\\ \\x^2-6x=(1)/(L^(2))-5\\ \\x^2-6x+9=(1)/(L^(2))-5 +9\\ \\x^2-6x+9=(1)/(L^(2))+4\\ \\(x-3)^2=(4L^(2)+1)/(L^(2))

Take the square root both sides


(x-3)=(+/-)\sqrt{(4L^(2)+1)/(L^(2))}\\ \\x=3(+/-)\frac{\sqrt{4L^(2)+1}}{L}

therefore


x=3+\frac{\sqrt{4L^(2)+1}}{L}


x=3-\frac{\sqrt{4L^(2)+1}}{L}

User Jhyot
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.